Impact generated to the Municipality of Ibagué with the embezzlement of the National Games of the year 2015 (2018)
In the rehearsal it is wanted to identify the impact generated by the embezzlement of the national games of the year 2015 to the municipality of Ibagué, the flaws presented in the process of state recruiting according to the limits of the law 80 of 1993, the internal check lack and of the control entities like de municipal controllership and the general controllership of the national, additional of the institutions like the IMDRI Municipal Institute for the Sport and the Recreation and COLDEPORTES, and the affectation generated the Ibagué inhabitants at economic, social level and of infrastructure, as well as the current administration has come developing its government plan in topics of investment entrance and that he is making at the present time for the recovery of the sport facilities that they were affected by the deviation of the resources of validity 2015.